2014
DOI: 10.1111/nmo.12479
|View full text |Cite
|
Sign up to set email alerts
|

Is fecal microbiota transplantation (FMT) an effective treatment for patients with functional gastrointestinal disorders (FGID)?

Abstract: This review aims to investigate the role of intestinal microbiota in the pathogenesis of FGID, the implications of FMT for the treatment of FGID, and the challenges encountered in measuring response to a specific intervention in patients with FGID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 109 publications
(187 reference statements)
1
61
0
5
Order By: Relevance
“…33 In IBS patients, alteration of intestinal microbiota has been linked to immune dysfunction and altered neurological functions, such as reduced pain threshold and increased anxiety, suggesting that restoration of normal intestinal homeostasis via FMT may result in symptomatic improvement. 34 Our results confirmed that FMT delivered through an NJ tube may relieve abdominal pain and bloating symptoms in CIPO patients. The microbiota plays a key role in the development and promotion of normal gut neuromotor function.…”
supporting
confidence: 78%
“…33 In IBS patients, alteration of intestinal microbiota has been linked to immune dysfunction and altered neurological functions, such as reduced pain threshold and increased anxiety, suggesting that restoration of normal intestinal homeostasis via FMT may result in symptomatic improvement. 34 Our results confirmed that FMT delivered through an NJ tube may relieve abdominal pain and bloating symptoms in CIPO patients. The microbiota plays a key role in the development and promotion of normal gut neuromotor function.…”
supporting
confidence: 78%
“…O TMF também tem sido evidenciado como alternativa de forma eficaz para outras doenças do trato GI, como a doença inflamatória do intestino, a síndrome do intestino irritável, a prisão de ventre crônica, entre outras patologias GI. Os sintomas são caracterizados pela diarreia predominante ou constipação predominante ou, ainda, ambos os sintomas, com ausência de quaisquer anomalias anatômicas ou exames bioquímicos identificáveis (29). Estas alterações podem estar relacionadas com a modificação da microbiota intestinal e possibilidade de alívio dos sintomas e cura da doença pode ser através do TMF.…”
Section: Resultsunclassified
“…116 The increasingly appreciated role of gut microbiota in the pathogenesis of FBDs and the imperfect current treatment can promote the use of FMT in selected patients with FBDs. [117][118][119] To date, few case series have reported outcomes of FMT for constipation and IBS, 120,121 but the results are promising. In a recent small study of FMT for refractory IBS (total of 13 patients: 9 IBS-D, 3 IBS-C, and 1 mixed IBS), a fecal suspension was infused into the distal duodenum or proximal jejunum via upper endoscopy.…”
Section: Fecal Microbiota Transplantationmentioning
confidence: 99%